Characterization of strains of Anaplasma marginale from clinical cases in bovine using major surface protein 1a in Uruguay - Parodi, Pablo; Armúa-Fernández, María T.; Schanzembach, Marcos; Mir, Daiana; Benítez-Galeano, María José; Rodríguez-Osorio, Nélida; Rivero, Rodolfo; Venzal, José M. (Frontiers in Veterinary Science, 2022)
The major surface protein 1a (MSP1a) gene has been used to characterise Anaplasma marginale genetic diversity. This pathogen causes significant productivity and economic losses to the cattle industry. The objective of the present study was to report the first characterisation of A. marginale genetic diversity in Uruguay based on MSP1a genotypes and their putative relationship with Rhipicephalus microplus. This cross-sectional study was conducted between 2016 and 2020. The study included whole blood samples from clinical cases of bovine anaplasmosis obtained from 30 outbreaks located in six Uruguay territorial departments. Diagnosis was performed using Giemsa-stained smears and confirmed by nested Polymerase Chance Reaction (nPCR) targeting the A. marginale major surface protein 5 gene. The genetic diversity of A. marginale strains was characterised by analysing the microsatellite and tandem repeats of MSP1a. Based on the microsatellite structure, four genotypes were identified. Genotype E was the most prevalent. Analysis of MSP1a tandem repeats showed 28 different strains from the combination of 31 repeats, with τ-10-15 being the most common. Repeats Γ, β, α, and γ were associated with the absence of R. microplus with statistical significance (p<0.05). Molecular observations showed that 46.7% of the strains identified in our samples lacked the ability to bind to tick cells; therefore, they were probably transmitted by other vectors. Strain genetic diversity provides valuable information for understanding the epidemiological behaviour of A. marginale and could contribute to the development of effective vaccines for the control of this disease.